2014
DOI: 10.2298/jsc140520077s
|View full text |Cite
|
Sign up to set email alerts
|

Hydro- and solvothermally-prepared ZnO and its catalytic effect on photodegradation of reactive orange 16 dye

Abstract: In this work, zinc oxide powders were obtained by two different techniques: hydro- and solvothermal synthesis starting from Zn(NO3)2 and Zn(CH3COO)2, respectively. The influence of synthetic procedure on the structural, microstructural, thermal and photocatalytic properties of the prepared ZnO powders was investigated. Both ZnO samples were further annealed at moderate conditions (300?C) to avoid grain growth and to remove traces of impurities. In all four cases a single-phase hexagonal ZnO w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Note that Raman spectroscopy provides a higher sensitivity to research the surface of nanomaterials especially in the presence of Ag nanoparticles [44], leading to the appearance of Raman features originated from the sample components with extremely low concentration. However, from our previous work [11], it was concluded that the presence of these traces impurities in prepared ZnO samples had a minor or no influence on their photocatalytic activity. It should be mentioned that XRPD and Raman analysis indicate that the commercial ZnO is probably more disordered than prepared ZnO samples which resulted in the decrease of photocatalytic activity of the commercial ZnO.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Note that Raman spectroscopy provides a higher sensitivity to research the surface of nanomaterials especially in the presence of Ag nanoparticles [44], leading to the appearance of Raman features originated from the sample components with extremely low concentration. However, from our previous work [11], it was concluded that the presence of these traces impurities in prepared ZnO samples had a minor or no influence on their photocatalytic activity. It should be mentioned that XRPD and Raman analysis indicate that the commercial ZnO is probably more disordered than prepared ZnO samples which resulted in the decrease of photocatalytic activity of the commercial ZnO.…”
Section: Discussionmentioning
confidence: 92%
“…Here, PVP, mutually with EG, played an important role in controlling the size and shape of the ZnO particles during the synthesis, causing the uniformity in size and morphology of the particles. The application of PVP as a surfactant was important for small crystallite and particle sizes and thus the use of this polymer is strongly recommended for the future research [53,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation